PERBANDINGAN HASIL PEMAPARAN CHATGPT-4 DENGAN PERPLEXITY AI DALAM PENGGUNAAN AI SEBAGAI ALAT BANTU UNTUK MELAKUKAN KAJIAN SERVICE BULLETIN EMBRAER LEGACY 600/650 - Yusup, Muhamad Yusup Kamal Arkan; Sofyan , Edi (Teknika STTKD: : Jurnal Teknik, Elektronik, Engine, 2024)
In the aviation industry, aircraft maintenance is crucial for ensuring safety and optimal performance. As technology evolves, digitalization and artificial intelligence (AI) are becoming vital for enhancing maintenance efficiency and accuracy. This study examines the use of AI, specifically ChatGPT-4 and Perplexity AI, to review Service Bulletins (SB) on the Embraer Legacy 600/650 and compares the results with manual reviews. The methodology involved three experienced reviewers manually examining two SBs, SB145LEG-33-0025 and SB145LEG-57-0015. These results were then compared with those generated by ChatGPT-4 and Perplexity AI, analyzing accuracy, processing time, and detail. Both AI platforms produced results similar to manual reviews, with minor differences in detail and interpretation. ChatGPT-4 was generally more accurate and detailed than Perplexity AI. Both AIs demonstrated significant potential in reducing the time and workload of SB assessments. The study concluded that AI could enhance efficiency in aircraft maintenance, especially in SB assessments, although human validation is still necessary to ensure accuracy and compliance with safety standards. Implementing AI in aviation maintenance can be an innovative step to address the industry's increasing complexity.